2022
DOI: 10.3389/fphys.2022.1096296
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and oxidative stress in salt sensitive hypertension; The role of the NLRP3 inflammasome

Abstract: Salt-sensitivity of blood pressure is an independent risk factor for cardiovascular disease and affects approximately half of the hypertensive population. While the precise mechanisms of salt-sensitivity remain unclear, recent findings on body sodium homeostasis and salt-induced immune cell activation provide new insights into the relationship between high salt intake, inflammation, and hypertension. The immune system, specifically antigen-presenting cells (APCs) and T cells, are directly implicated in salt-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…The rationale behind the purported activities of omega 3 fatty acids on the endothelium and vasomotion is manifold. For example, omega 3 fatty acids are anti-inflammatory molecules [ 136 ] and inflammation greatly participates in the development of, e.g., arterial stiffness [ 117 ], impaired vasomotion [ 137 ], and hypertension [ 138 ]. Moreover, that are — paradoxically — anti- rather than pro-oxidant [ 139 , 140 ], via molecular mechanisms that have been largely elucidated and include, e.g., inhibition of NADPH oxidase 4 (Nox 4), V sPLA 2 , and cyclooxygenases, as well as reduced superoxide production [ 140 ], thereby maintaining an adequate “peroxide tone” [ 141 ].…”
Section: Methodsmentioning
confidence: 99%
“…The rationale behind the purported activities of omega 3 fatty acids on the endothelium and vasomotion is manifold. For example, omega 3 fatty acids are anti-inflammatory molecules [ 136 ] and inflammation greatly participates in the development of, e.g., arterial stiffness [ 117 ], impaired vasomotion [ 137 ], and hypertension [ 138 ]. Moreover, that are — paradoxically — anti- rather than pro-oxidant [ 139 , 140 ], via molecular mechanisms that have been largely elucidated and include, e.g., inhibition of NADPH oxidase 4 (Nox 4), V sPLA 2 , and cyclooxygenases, as well as reduced superoxide production [ 140 ], thereby maintaining an adequate “peroxide tone” [ 141 ].…”
Section: Methodsmentioning
confidence: 99%
“…RAAS is a critical regulator of blood pressure, and various components of the RAAS signalling pathway can directly impact immune cell function [60]. We recently investigated in-vitro expression of RAAS-related genes in human monocytes from healthy individuals in response to high sodium and found that expression of these genes did not correlate with salt-induced activation of myeloid immune cells in salt-sensitive hypertension [61]. These results suggest that RAAS may not play a significant role in regulating immune cell ENaC in SSBP.…”
Section: Regulation Of Immune Cell Epithelial Sodium Channelmentioning
confidence: 99%
“…Inflammasome activation is another recent discovery involved in the relationship between inflammation, autoimmunity, and SSBP [ 62 ]. Our group recently elucidated the role of NOD-like receptor family pyrin domain containing 3 (NLRP3) in SSBP [ 62 , 63 ▪▪ ] (Fig. 3 ).…”
Section: Downstream Signalling In Epithelial Sodium Channel Activated...mentioning
confidence: 99%
“…Containing 3 (NLRP3) inflammasome, leading to the production of inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), IL-1β, and IL-6 [105,109,110]. The increased production of inflammatory cytokines coupled with the reduced production of NO resulting from ROS reactions leads to the stiffening of blood vessels and endothelial activation/dysfunction that contributes to hypertension and CVDs [109].…”
Section: Proposed Glycocalyx-salt Interaction Mechanisms Contributing...mentioning
confidence: 99%